Implementasi Metode ARIMA-GARCH Terhadap Peramalan Konversi Mata Uang Yen ke Rupiah - Bintang Sirius; Widyanti Rahayu; Yudi Mahatma (Program Studi Matematika Universitas Negeri Jakarta, 2023)
Buying and selling transactions are always used by humans to meet their needs. One of the transaction tools used is money. Each country has its own currency including Japan, with Yen continues to experience a significant decline throughout April 2022 exceeding 5-10%. Therefore, it is necessary to anticipate the rate of increase/decrease in Yen. After testing and forecasting, it was concluded that the most appropriate model for analyzing the data in this study was the ARIMA(3,1,3) - GARCH (1,1) model. This is because the model can overcome the homogeneity of the data. The conversion of Yen to Rupiah currency from August 2022 to July 2023 can be predicted to have fluctuations, and produce a MAPE value of 19.29%, which indicates that the precision level of the ARIMA(3,1,3) - GARCH(1,1) is good enough to use for the conversion data.